2015
DOI: 10.4103/0975-7406.155894
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of forensic odontology: An overview

Abstract: Forensic dentistry or forensic odontology admits dentists’ participation or identification of the victim and assisting legal and criminal issues. It refers to the proper handling, examination, identification and evaluation of dental evidence. This article summarizes the evolution of forensic odontology that started right from Garden of Eden to the modern scenario in identification of the gang rape case which happened in the state capital. Forensic dentistry plays a significant role in identifying the victims o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Forensic odontology (FO) is a very distinctive branch of dentistry, which deals with the various aspects of forensic investigations. The role of FO is widely known and has been proved in the literature through various laboratory investigations and actual incidences such as victim identifications in mass disasters ( Divakar, 2017 ; Balachander et al, 2015 ). FO helps in victim identification by virtue of variety of unique means, which has potential to confirm the age, gender, and person identification ( Divakar, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Forensic odontology (FO) is a very distinctive branch of dentistry, which deals with the various aspects of forensic investigations. The role of FO is widely known and has been proved in the literature through various laboratory investigations and actual incidences such as victim identifications in mass disasters ( Divakar, 2017 ; Balachander et al, 2015 ). FO helps in victim identification by virtue of variety of unique means, which has potential to confirm the age, gender, and person identification ( Divakar, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…DA et al (2015) demonstrated the accuracy of dental age estimation from TCI of mandibular premolars and molars of using digital panoramic radiographs are precise, non-invasive, not time consuming, not required highly specialised equipment. Priyadharsini et al (2015) The study by Drusini (2008) reported CPCI as a method that can be easily used to estimate age both in living individuals and skeletal material of unknown age in a forensic context. (Drusini, 2008) The above studies has been proved that the digital radiographic techniques are used to estimate the dental age because it is a simple tool to view and measure the reduction in the pulp chamber.…”
Section: Discussionmentioning
confidence: 99%
“…(A ify, 2014;Veera et al, 2014) Non invasive radiography been developed for measurements of reduction in pulp cavity and secondary dentin formation. (Sakhdari et al, 2015;Priyadharsini et al, 2015) Size of pulp chamber, will reduce with age, shows a relationship with chronological age. (DA et al, 2015;Veera et al, 2014;Mehta et al, 2017) However, the limitation of panoramic radiographs has been reported not adequate for accurate age estimation in the past four decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was the Delhi gang rape case where the forensic odontologist linked the dentition of the two accused to the bite marks on the victim. [15]…”
Section: The Current Scenario In Indiamentioning
confidence: 99%